The Impact of Service Quality, Product Variety, and Price Perception on Brand Switching Providers IndiHome in Surabaya - Ristiana, Ega Rifa; Ariescy, Reiga Ritomiea (LPPM Universitas Jambi, 2026)
The competition growth in Indonesia’s internet service provider industry has given consumers a wide range of provider options, thereby increasing the potential for brand switching. This study aims to analyze the influence of service quality, product variety, and price perception on brand switching among IndiHome providers in Surabaya. This study employs a quantitative approach using the explanatory research method. The sampling technique utilized purposive sampling, with a sample size of 115 respondents who had previously used IndiHome and switched providers. Data collection was conducted through the distribution of questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that service quality has a non-significant negative effect on brand switching, while product variety and price perception have significant positive effects on brand switching among IndiHome customers in Surabaya. The findings imply that internet service providers should prioritize competitive pricing and diverse product offerings to reduce customer switching. In addition, improving service quality alone may not be sufficient to retain customers, suggesting the need for a more comprehensive customer retention strategy.